THE HISTORICAL DEFEAT OF THE FEMALE SEX - Kant, Astha (THE PRIMARY TEACHER, 2009)
Gender inequality poses a serious barrier to access a healthy life. This inequality stems out of patriarchy. Patriarchy not only defines the socially constructed roles of men and women in a society but also internalises them in its members. These internalised norms and roles have a huge bearing on the health of both men and women. It has been realised that it is women who are subjected to be victimised of the inequality while men are entitled to be superior. This article taking Marx’s perspective, explores the status of most of the married women in a patriarchal society, how she is perceived as an instrument of reproduction which makes her alienated from the ‘product as well as the process of reproduction’. The paper further questions the taken for granted social phenomenon of superiority of men, which is ‘bracketed’ in a society which hinders good reproductive health to women.